O-acetylation of the serine-rich repeat glycoprotein GspB is coordinated with accessory Sec transport - Seepersaud, Ravin (PLoS Pathog, 2017)
The serine-rich repeat (SRR) glycoproteins are a family of adhesins found in many Gram-positive bacteria. Expression of the SRR adhesins has been linked to virulence for a variety of infections, including streptococcal endocarditis. The SRR preproteins undergo intracellular glycosylation, followed by export via the accessory Sec (aSec) system. This specialized transporter is comprised of SecA2, SecY2 and three to five accessory Sec proteins (Asps) that are required for export. Although the post-translational modification and transport of the SRR adhesins have been viewed as distinct processes, we found that Asp2 of Streptococcus gordonii also has an important role in modifying the SRR adhesin GspB. Biochemical analysis and mass spectrometry indicate that Asp2 is an acetyltransferase that modifies N-acetylglucosamine (GlcNAc) moieties on the SRR domains of GspB. Targeted mutations of the predicted Asp2 catalytic domain had no effect on transport, but abolished acetylation. Acetylated forms of GspB were only detected when the protein was exported via the aSec system, but not when transport was abolished by secA2 deletion. In addition, GspB variants rerouted to export via the canonical Sec pathway also lacked O-acetylation, demonstrating that this modification is specific to export via the aSec system. Streptococci expressing GspB lacking O-acetylated GlcNAc were significantly reduced in their ability bind to human platelets in vitro, an interaction that has been strongly linked to virulence in the setting of endocarditis. These results demonstrate that Asp2 is a bifunctional protein involved in both the post-translational modification and transport of SRR glycoproteins. In addition, these findings indicate that these processes are coordinated during the biogenesis of SRR glycoproteins, such that the adhesin is optimally modified for binding. This requirement for the coupling of modification and export may explain the co-evolution of the SRR glycoproteins with their specialized glycan modifying and export systems.